THE INTRODUCTION OF GIS AND GPS THROUGH LOCAL HISTORY TEACHING IN PRIMARY SCHOOL - Nikos LAMBRINOS; Fani ASIKLARI (European Journal of Geography)
Taking into consideration the fact that every place has a number of sites which are worth visiting because they are connected to the local history, we decided to motivate the pupils of 4th, 5th and 6th grade of a small village in Western Macedonia, Greece, in a kind of a treasure hunt (fieldtrip) enriched with the use of compass, GPS and GIS generated maps. The results of the project show that the use of high technology is feasible even from the age of 10, provided that the lesson plan is well designed. High technology applications, like GIS and GPS, can be easier implemented through interdisciplinarity. Finally, a geography related questionnaire was provided to the pupils at the end of the project which showed that the improvement in geography issues was up to 94% among the pupils and in some cases approached the ultimate success compared to the lack of previous knowledge